On the Number of Limit Cycles of a Piecewise Quadratic Near-Hamiltonian System - Jing Tian (Abstract and Applied Analysis)
This paper is concerned with the problem for the maximal number of limit cycles for a quadratic piecewise near-Hamiltonian system. By using the method of the first order Melnikov function, we find that it can have 8 limit cycles.